Pendidikan untuk Peradaban Digital: Telaah Filsafat Pendidikan atas Naskah Akademik Pembelajaran Koding dan Kecerdasan Artifisial - Hidayat, Fahri; Fahri; Nugroho, Ischak Suryo (Paedagogie, 2026)
This study aims to analyze philosophically the Academic Manuscript on Coding and Artificial Intelligence Learning for Primary and Secondary Education (Naskah Akademik Pembelajaran Koding dan Kecerdasan Artifisial pada Pendidikan Dasar dan Menengah) in order to reconstruct the educational paradigm that underpins it. The research employs a qualitative library research approach using document analysis and philosophical hermeneutics. The primary data consist of the academic manuscript published by the Agency for Standards, Curriculum, and Educational Assessment. The analysis is conducted through three dimensions of educational philosophy: ontology, epistemology, and axiology. The findings reveal that, ontologically, the academic manuscript constructs human beings as adaptive, creative, collaborative, and responsible subjects within the digital civilization. Epistemologically, coding and artificial intelligence learning are grounded in a constructivist paradigm that integrates computational thinking, problem-solving, data literacy, and artificial intelligence literacy as the foundation of digital knowledge. Axiologically, the development of digital competencies is directed toward fostering digital ethics, character formation, and social responsibility. This study reconstructs the concept of Education for Digital Civilization as a philosophy of education paradigm that positions human beings as the center of digital transformation through a human-centered digital civilization